2013
DOI: 10.1038/cr.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-mediated cleavage of C53/LZAP protein causes abnormal microtubule bundling and rupture of the nuclear envelope

Abstract: Apoptotic nucleus undergoes distinct morphological and biochemical changes including nuclear shrinkage, chromatin condensation and DNA fragmentation, which are attributed to caspase-mediated cleavage of several nuclear substrates such as lamins. As most of active caspases reside in the cytoplasm, disruption of the nuclear-cytoplasmic barrier is essential for caspases to reach their nuclear targets. The prevailing proposed mechanism is that the increase in the permeability of nuclear pores induced by caspases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
(59 reference statements)
0
40
0
Order By: Relevance
“…The disruption of nuclear scaffold (also known as nuclear matrix) proteins, such as lamins and the NPC, is increased in apoptotic cell death 28 . A recent study showed that caspase mediated the induction of NE disruption during apoptosis, and the results were confirmed through fluorescence intensity, measured by confocal microscopy 29 . However, the changes that occur in cell adhesion and the NE, and how these alterations and characteristics correlate to necrotic and apoptotic cell death, are not clearly understood.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The disruption of nuclear scaffold (also known as nuclear matrix) proteins, such as lamins and the NPC, is increased in apoptotic cell death 28 . A recent study showed that caspase mediated the induction of NE disruption during apoptosis, and the results were confirmed through fluorescence intensity, measured by confocal microscopy 29 . However, the changes that occur in cell adhesion and the NE, and how these alterations and characteristics correlate to necrotic and apoptotic cell death, are not clearly understood.…”
mentioning
confidence: 63%
“…Structural analysis of ESCs showed the presence of irregular and wide-shaped NEs in the intermembrane space of ESCs, in comparison to differentiated cells, through use of fluorescence staining and electron microscopy 55 . Further, apoptotic cell death showed disassembling of NE proteins, and structural changes in nucleus, such as shrinkage, NE rupture, irregular nucleus shape, and DNA leakage, which were measured by fluorescence staining and electron microscopy 29 56 57 . However, the study of structural and topographical changes of the NE using morphometric analysis is not ideal, due to the indirect detection of change by current methods, and the detection of only partial changes.…”
Section: Discussionmentioning
confidence: 99%
“…After all, PC12 cell line is a cancer cell line, the in vivo effect and mechanism of DSePA need further evaluation. Apoptosis, a programmed cell death, plays an essential role in maintaining the homeostasis in the brain [32,33]. Caspase, a family of cysteine proteases, can be activated in response to apoptotic stimuli and play essential roles in launching cell apoptosis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, C53 protein, one of RCAD downstream targets, has been shown to be a microtubule-binding protein. 41 C53 KO leads to cell cycle defects and early embryonic lethality, 42 and depletion of C53 protein in tissue culture cells dramatically decreases the numbers of several types of intracellular vesicles (our unpublished observation). Therefore, we postulate that the RCAD/C53/DDRGK1 complex has an important role in regulation of intracellular vesicle trafficking.…”
Section: Discussionmentioning
confidence: 99%